Modeling and Analysis of Transformerless High Gain Buck-boost DC-DC Converters - Vu Tran; Mufeed MahD (Institute of Advanced Engineering and Science, 2014)
This paper proposes a transfomerless switched capacitor buck boost converter model, which provides higher voltage gain and higher efficiency when compared to the conventional buck boost converter. The averaged model based on state-space description is analyzed in the paper. The simulation results are presented to confirm the capability of the converter to generate high voltage ratios. The comparison between the proposed model and the traditional model is also provided to reveal the improvement. The proposed converter is suitable for for a wide application which requires high step-up DC-DC converters such as DC micro-grids and solar electrical energy.DOI: http://dx.doi.org/10.11591/ijpeds.v4i4.6386